The Potential Yield of Sunflowers on Coastal Land with Several Dosages of Mycorrhizae and Chicken Manure Fertilizer - Obel Obel (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2023)
Sunflower (Helianthus annuus L) is one of the best sources of vegetable oil because of the high quality of the oil. This plant is a leading commodity that has the potential to be developed because, from an economic point of view, it has various benefits as a food ingredient, raw material industry, raw materials, and medicines raw materials for beauty products. Today's sunflower development is more diverted to marginal lands. One of them is the use of coastal areas, which have various economic and technical problems. For this reason, it is necessary to implement innovations that can support sunflower cultivation in coastal areas. One of them is by applying mycorrhiza and adding chicken manure. This study aims to determine the effect of mycorrhiza and chicken manure doses on sunflower yields in coastal areas. This research was conducted using a randomized block design consisting of two factors: mycorrhiza and chicken manure, which were repeated three times. The results showed that mycorrhiza and chicken manure could increase the components of several characteristics and sunflower yields in coastal areas.